EU agricultural policy and productivity of soil in countries varying in terms of intensity of agricultural production - Smędzik-Ambroży Katarzyna; Majchrzak Adam (Management)
It was emphasised in the work whether there are differences in soil productivity of FADM farms from countries belonging to EU-15 and EU-12, and whether CAP subsidies impact the degree of these differences. For this purpose, a comparative analysis was conducted for the soil productivity indicators (taking into account the value of CAP subsidies in the value of production from agricultural activity and without such subsidies) as well as a statistical assessment of differences between those indicators in EU-15 and EU-12 countries based on the Mann-Whitney U test. EU-FADN data was used in the work. The timeframe covered the period of 2007-2013, the spatial scope covered EU-27 countries while the subject scope covered farms representative for particular EU-15 and EU-12 countries. A hypothesis was made that including subsidies from the Common Agricultural Policy in the total production generated from farming causes absence of the significance of differences, in the productivity of soils from EU- 15 and EU-12 countries. As a result of the conducted analyses, it was confirmed that CAP subsidies increase the difference in the scope of soil productivity between farms from EU-15 and EU-12 countries. A bigger level of differences occurred between FADN farms from countries composing EU-15.